IMPLEMENTASI ANGGARAN TENAGA KERJA DALAM PERENCANAAN KEUANGAN PT INDUSTRI TELEKOMUNIKASI INDONESIA (Persero) - Dinda Dwi Aprillia; Anggie Pricyla Sianturi; Muhammad Rizal (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The direct labor budget is a key component in financial planning, serving not only to estimate labor costs but also to optimize human resource allocation and control expenses. This study employs a qualitative descriptive approach through an in-depth review of PT INTI (Persero)’s 2022 RKAP and related literature to understand the implementation of the direct labor budget. The analysis compares the planned budget with actual realization by measuring wage rate variances and labor efficiency. The results reveal that the implementation of the budget significantly enhances cost efficiency and strengthens interdepartmental coordination. These findings identify key areas of inefficiency that can be improved to support more effective and measurable cost control strategies. Thus, the study provides a strategic foundation for improving financial management that is responsive to operational dynamics and market competition